Effect of dietary magnesium supplementation on serum magnesium concentration and performance of female West African dwarf (Fouta djallon) goats - AINA, A B J (The Indian Journal of Animal Sciences, 2013)
An experiment was conducted with 16 female West African dwarf (Fouta djallon) goats, 6 -to 12 - months old, weighing 5 tp 10 kg to estimate their serum magnesium concentration and performance using depletion-repletion approach. West African dwarf goats require higher dietary magnesium supplementation for maximum serum concentration and growth rate than either temperate sheep or cattle. Besides growth rate, feed conversion ratio also increased with increasing dietary magnesium supplementation while magnesium requirement for maintenance in West African dwarf goat is low (0.001 83kg/w0.75 kg). On average the optimum growth rate (0.094kg/day), dry-matter intake (0.045kg/Wo.75kg) and serum magnesium-concentration (4mg Mg/l 00mlÂ·serum) were significantly induced by 0.50kg Mg/100kg diet(DM). However, magnesium deficiency in West Africa dwarf goats that causes loss of weight, appetite and serum magnesium deficiency below 1.03Mg Mg/ 100ml could be rectified through a 42-day dietary magnesium repletion period.